Human β-defensin 1 in follicular fluid and semen: impact on fertility - Zupin, Luisa (J Assist Reprod Genet, 2019)
PURPOSE: β-defensins are antimicrobial peptides expressed at mucosal level of male and female genito-urinary tract, where they exert protective functions against infections, possibly preserving human health and fertility. In our study, we investigated the possible involvement of β-defensins in female and male infertility in Italian infertile couples (i) evaluating the presence of human β-defensin 1 (hBD-1) in follicular fluid (FF) and its correlation with in vitro fertilization (IVF) outcomes; (ii) investigating the relationship between hBD-1 levels in semen and IVF outcomes (comprising correlation with sperm parameters); and (iii) exploring the effect of hBD-1 peptide on spermatozoa motility in vitro. METHODS: A perspective observational analytic pilot study was conducted. hBD-1 concentration was measured with ELISA assay in FF and semen from 50 couples that underwent assisted procreation technique procedures due to infertility status. Moreover, hBD-1 exogenous peptide was administered to 29 normozoospermic semen and their motility was recorded. RESULTS: hBD-1 was detected in FF and its levels were significantly higher in women with good fertilization rate (≥ 75%), respect to those with a poor fertilization rate (< 75%). The hBD-1 semen concentrations in oligo-asthenozoospermic subjects were significantly lower than that in normozoospermic men. Instead, hBD-1 level in sperm and FF not correlated with pregnancy rate. Finally, incubation of sperm with exogenous hBD-1 significantly increased progressive motility after 1 h and 24 h. CONCLUSIONS: Being aware of the relatively small sample size and medium power, our results possibly suggest that hBD-1 could influence oocyte and sperm quality, and could improve, when exogenously added, sperm motility. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-019-01409-w) contains supplementary material, which is available to authorized users.